Economic aspects of button mushrooms in Mid-Hills of Himachal Pradesh - Mahajan, Girish; Walia, Saina; Thakur, Rajesh (Asian Journal of Agriculture and Rural Development, 2026)
Button mushroom cultivation in Himachal Pradesh is economically significant, providing a profitable venture for farmers, contributing to rural income generation, and offering a valuable source of protein and other nutrients. The present study was designed with the primary objective of examining the economics of button mushroom cultivation in the study area. Primary data were collected from 60 mushroom growers residing in 7 randomly selected blocks of the purposively chosen Kangra district. The respondents were categorized into two groups, small and large, based on the number of compost bags they maintained, using the cumulative square-root frequency method. The results indicated that the fixed cost of production per 100 bags varied from 32.80% on small farms to 22.97% on large farms, while variable costs ranged from 67.20% on small farms to 72.21% on large farms. The gross return per 100 bags of button mushroom ranged from Rs. 40,587 to Rs. 47,109, whereas the net return over total cost per kilogram varied from Rs. 34.08 to Rs. 63.73 on small and large farms, respectively. The break-even output, where growers neither made a profit nor incurred a loss, was 100 kg overall, with 150 kg for small farms and 69 kg for large farms. Factors influencing mushroom production included the number of compost bags, human labor, expenditure on plant protection materials, and the management index, which are significant variables affecting production on the sampled farms.